Sustained Replication of Synthetic Canine Distemper Virus Defective Genomes In Vitro and In Vivo - Tilston-Lunel, Natasha L.; Welch, Stephen R.; Nambulli, Sham; de Vries, Rory D.; Ho, Gregory W.; Wentworth, David E.; Shabman, Reed; Nichol, Stuart T.; Spiropoulou, Christina F.; de Swart, Rik L.; Rennick, Linda J.; Duprex, W. Paul (mSphere, 2021)
Defective interfering (DI) genomes have long been considered inconvenient artifacts that suppressed viral replication in vitro . However, advances in sequencing technologies have led to DI genomes being identified in clinical samples, implicating them in disease progression and outcome. Defective interfering (DI) genomes restrict viral replication and induce type I interferon. Since DI genomes have been proposed as vaccine adjuvants or therapeutic antiviral agents, it is important to understand their generation, delineate their mechanism of action, develop robust production capacities, assess their safety and in vivo longevity, and determine their long-term effects. To address this, we generated a recombinant canine distemper virus (rCDV) from an entirely synthetic molecular clone designed using the genomic sequence from a clinical isolate obtained from a free-ranging raccoon with distemper. rCDV was serially passaged in vitro to identify DI genomes that naturally arise during rCDV replication. Defective genomes were identified by Sanger and next-generation sequencing techniques, and predominant genomes were synthetically generated and cloned into T7-driven plasmids. Fully encapsidated DI particles (DIPs) were then generated using a rationally attenuated rCDV as a producer virus to drive DI genome replication. We demonstrate that these DIPs interfere with rCDV replication in a dose-dependent manner in vitro . Finally, we show sustained replication of a fluorescent DIP in experimentally infected ferrets over a period of 14 days. Most importantly, DIPs were isolated from the lymphoid tissues, which are a major site of CDV replication. Our established pipeline for detection, generation, and assaying DIPs is transferable to highly pathogenic paramyxoviruses and will allow qualitative and quantitative assessment of the therapeutic effects of DIP administration on disease outcome. IMPORTANCE Defective interfering (DI) genomes have long been considered inconvenient artifacts that suppressed viral replication in vitro . However, advances in sequencing technologies have led to DI genomes being identified in clinical samples, implicating them in disease progression and outcome. It has been suggested that DI genomes might be harnessed therapeutically. Negative-strand RNA virus research has provided a rich pool of natural DI genomes over many years, and they are probably the best understood in vitro . Here, we demonstrate the identification, synthesis, production, and experimental inoculation of novel CDV DI genomes in highly susceptible ferrets. These results provide important evidence that rationally designed and packaged DI genomes can survive the course of a wild-type virus infection.